Pineapple peel as alternative substrate for bacterial nanocellulose production - Lee, Adriana Connie; Md Salleh, Madihah; Ibrahim, Mohamad Faizal; Bahrin, Ezyana Kamal; Jenol, Mohd Azwan; Abd-Aziz, Suraini (Springer, 2022)
Due to its flexible properties, bacterial nanocellulose (BNC) has been attracting tremendous attention. In this study, BNC was produced by Acetobacter xylinum ATCC2376 and a local isolate, namely, Bacillus cereus MMS1. The production of BNC was done by utilising pineapple peel extract (PPE) (wastes discarded after cutting the fruit) as the alternative carbon source substituting the commercial D-glucose (control) in Hestrin–Schramm (HS) medium under agitated conditions. This research is aimed to investigate the synthesis of BNC by an isolated bacterial strain from termite’s gut using an agro-industrial waste which is the pineapple peel extract. Six bacterial strains, namely, F8, F5, M1, M6, H7 and H11, were screened and identified for potential BNC producer. The selected bacterial strain was identified as Bacillus cereus MMS1 using 16S rRNA nucleotide sequences. Then, the production of BNC was done by B. cereus MMS1 using pineapple peel extract, while A. xylinum ATCC2376 acted as a control. The BNC production in this study was attained at 2% (w/v) glucose concentration, 12 days of incubation period and 150 rpm agitation speed which was 5.83 g/L by A. xylinum ATCC2376 in HS medium using commercial glucose as carbon source. Meanwhile, 4.42 g/L and 2 g/L of BNC were produced by B. cereus MMS1 after 12 days of incubation with an initial concentration of 2% (w/v) using commercial glucose and pineapple peel extract, respectively.